The effect of banking sector reforms on interest rate spread: Evidence from Ghana - Cornelius Yao Azumah; Anthony Owusu-Ansah; Godfred Amewu; Williams Ohemeng (Cogent Economics & Finance, 2023)
The wide interest rate spread has been a matter of concern for many developing economies. In Ghana, the perception is that the interest rate spread is too wide and that banks have linked it to various variables affecting them. This study examines the effect of banking sector reforms on bank interest rate spread in Ghana over the period 2008-2020, using an unbalanced panel-data dynamic-equation regression model. The findings reveal that bank size, profitability, gross domestic product, and inflation rate significantly influence Ghana's bank interest rate spread. Results also suggest that these factors account for determining the interest rate spread in the universal banking industry in Ghana. The industry needs to mitigate the interest rate spread by improving the macroeconomic environment, address industry-specific issues, strengthen institutional systems, such as governance and supervision, and also continue to ensure stability in the political environment. The study provides valuable insights regarding the design and formulation of competitive policies and regulatory changes on interest rate regimes, to help promote the competitiveness of the universal banking industry in the country. Policymakers and regulators should emphasize enterprise risk management practices in Ghana's universal banking industry to check credit risk and other risk forms.
Keywords: 330; bank-specific factors; Banking reforms; interest rate spread; macroeconomic factors; regulatory changes; two-step system GMM